Mobility Management Technologies for 6G-Oriented Low Earth Orbit Satellite Communication Systems - LU Hang; ZHANG Jiaxin; WANG Haixu (天地一体化信息网络)
The LEO satellite system, with its unique advantages such as global coverage and low latency, combined with the direct satellite-to-ground communication method, has shown great potential in enhancing global communication capabilities and will become an important part of next-generation communication network. However, the system faces many challenges in mobility management, including frequent satellite handovers, complex signaling interactions, and allocation and management of handover resources. To better advance the development of mobility management in LEO satellite communication systems, this paper first provided an overview of recent progress in mobility management related to architecture design, handover mechanisms, and traffic continuity management. It then presented mobility management enhancement technologies for 6G LEO satellite systems. Finally, this paper discussed the opportunities and challenges that future LEO satellite communication systems may face in mobility management.